Seismic Retrofit using ETABS (International Journal of Innovative Research in Engineering & Management, 2022)
In India, Multi-storied structures built are  deficient of land and have to carry maximum load.  Earthquake could be a circumstance which might result in  the failure of the structure. Buildings are to be created so  that they are safe to live in and the structure before failure  should possess ductile property. To prevent structures from  failing and from serious damages the structures before  construction should be analyzed for its seismic performance  along with support reactions and wind calculations both are  to be included in the design of an earthquake resistant  structure. The primary objective of present study is to make  earthquake resistant structure by retrofitting its columns and  the process is known as column jacketing. The retrofitted  structure is analyzed in the E-tabs software. For this  purpose, a retrofitted G+5residentialbuilding is considered.  Calculations are done for an earthquake in seismic zone V.  To guarantee the safety of the structure all the forces acting  on the structure including the lateral loads due to wind and  seismic excitations are considered. Because of the jacketing  the column strength and the overall stability of the structure  will increase. By using IS Code (IS 15988-2013), the  jacketing will be done in E-tabs software. After the  jacketing the various responses including bending moment,  shear force of existing building will be studied under  various loads for an earthquake in seismic zone V.
Keywords: Multi-Story building; Retrofitting measures; Column Jacketing; ETABS v18; Section Designer; Modelling; Story Drifts; Maximum story displacement